Musculoskeletal trauma and all-cause mortality in India: a multicentre prospective cohort study. (27th April 2015) - Foote, Clary Jefferson; Mundi, Raman; Sancheti, Parag; Gopalan, Hitesh; Kotwal, Prakash; Shetty, Vijay; Dhillon, Mandeep; Devereaux, Philip; Thabane, Lehana; Aleem, Ilyas; Ivers, Rebecca Q; Bhandari, Mohit; et al.
Abstract: Background: There is little data in low-income and middle-income countries (LMICs) quantifying the burden of fractures and describing current practices. The aim of the study was describe the severity of musculoskeletal injuries in LMICS and identify modifiable factors that predict subsequent early all-cause mortality. Methods: We did a multicentre, prospective, observational study of patients who presented to 14 hospitals across India for musculoskeletal trauma (fractures or dislocations). Patients were recruited during an 8-week period, between November, 2011, and June, 2012, and were followed for 30-days or hospital discharge, whichever occurred first. Primary outcome was all-cause mortality with secondary outcomes of reoperation and infection. Logistic regression analyses were conducted to identify factors associated with all-cause mortality. Findings: We enrolled 4822 patients, but restricted analyses to 4612 (96%) patients who had complete follow-up. The majority (56·2% younger than 40 years old) of trauma patients were young (mean age 40·9 years [SD 16·9]) and 3148 (68%) were men. 2344 (518%) patients sustained trauma as a result of a road traffic accident. The most common musculoskeletal injury was a fracture (4514 [98%]) and 707 patients (15%) incurred an open fracture. Less than a third of musculoskeletal trauma patients (1374 [29%]) were transported to hospital by ambulance, and one in six patients (18%) arrived at the hospital later than 24 h after sustaining their injury. Over a third (239 [35%] of 707) of open fractures were definitively stabilised later than 24 h. 30-day mortality was 1·7% (95% CI 1·4–2·2) for all patients and 2·1% (95% CI 1·5–2·7) among road traffic victims (p=0·005). Musculoskeletal trauma severity including the number of fractures (3·1 [95% CI 2·4–3·9]) and presence of an open fracture (2·1 [95% CI 1·2–3·4]) significantly increased the odds of all-cause mortality. Interpretation: Musculoskeletal trauma severity, particularly road related, is a key predictor of subsequent mortality. Improvement in road safety policies, and improvements in access to emergency medical services and timely orthopaedic care are critical to mitigate the burden of injury worldwide. Funding: Regional Medical Associates, AO International, Hamilton Health Sciences Trauma Fund.